Da Giansenio a Pascal: nascita e sviluppi del giansenismo dall’(im)possibilità dei comandamenti alla critica del potere prossimo - Chiara Catalano (Noctua)
This essay stems from the origins of Jansenism, from the publication of Cornelius Jansenius’s Augustinus (1640) to the conflict between Jansenists and Jesuits (1641–1643; 1649–1653), culminating in the condemnation of the Five Propositions. It examines the meaning of the First Proposition on the impossibility of observing the commandments in Augustine and, through a comparison between Jansenius and Pascal, explores the same theme in the Provinciales and Écrits sur la grâce. It focuses on the notion of proximate power and the criticism of the Jesuits, as well as the alleged proximity to the Thomists. The analysis highlights recurring themes in Jansenius and Pascal, derived from their common Augustinian reference, but also notes some contextual and stylistic differences between the two authors.